2005
DOI: 10.1071/wf04062
|View full text |Cite
|
Sign up to set email alerts
|

Lethal soil temperatures during burning of masticated forest residues

Abstract: Mastication of woody shrubs is used increasingly as a management option to reduce fire risk at the wildland–urban interface. Whether the resulting mulch layer leads to extreme soil heating, if burned, is unknown. We measured temperature profiles in a clay loam soil during burning of Arctostaphylos residues. Four mulch depths were burned (0, 2.5, 7.5 and 12.5 cm), spanning typical conditions at forested sites in northern California with dense pre-mastication shrub cover. Two soil moisture contents were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(105 citation statements)
references
References 13 publications
3
100
1
1
Order By: Relevance
“…Soil temperatures reaching 100 • C can be lethal to the soil microbes [22] and temperatures ranging 200-500 • C cause reductions of soil carbon (C) and nitrogen (N), aggregate stability, and thermal conductivity [20]. While numerous studies have documented soil temperature flux during slash pile burning (e.g., [23,24]), we could find no information on soil heating while using ACB. We hypothesize that temperatures could be much higher since larger volumes of wood can be burned at once and the high turbulence associated with air movement across the burning wood can increase the chamber temperature to ≥980 • C. However, although the impacts of burning on belowground processes are highly variable [25], lack of in situ heat transfer measurements hinders the evaluation of heating damage from ACB and, perhaps, an increased use in areas with excess woody residues.…”
Section: Introductioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Soil temperatures reaching 100 • C can be lethal to the soil microbes [22] and temperatures ranging 200-500 • C cause reductions of soil carbon (C) and nitrogen (N), aggregate stability, and thermal conductivity [20]. While numerous studies have documented soil temperature flux during slash pile burning (e.g., [23,24]), we could find no information on soil heating while using ACB. We hypothesize that temperatures could be much higher since larger volumes of wood can be burned at once and the high turbulence associated with air movement across the burning wood can increase the chamber temperature to ≥980 • C. However, although the impacts of burning on belowground processes are highly variable [25], lack of in situ heat transfer measurements hinders the evaluation of heating damage from ACB and, perhaps, an increased use in areas with excess woody residues.…”
Section: Introductioncontrasting
confidence: 41%
“…Busse et al [24] mimicked broadcast burning after mastication and reported the maximum soil surface temperatures reached 500-600 • C (dry soil) and 400-500 • C (wet soil), and observed peak temperatures at 10 cm ranged 40-105 • C. Neary et al [22] also observed severe soil heating; 700 • C at surface over 250 • C at 10 cm depth, and greater than 100 • C at 22 cm depth. In the extreme, soil heating has been observed 1.36 m deep under heavy slash pile [23].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Higher temperatures were likely prevented both by the presence of a mulching agent (i.e. the surface cover of litter, stones and mosses) and the high soil humidity [8]. However, high moisture conditions can be particularly lethal for soil microbes due to faster heat penetration and a smaller fraction of dormant organisms [11,27,42].…”
Section: Fire Effects On the Community Structure And Ecosystem Functionsmentioning
confidence: 99%
“…Litter depths were rarely great enough (i.e. .7.5 cm) to allow smouldering fires, which can maintain lethal temperatures for over an hour and result in root death (Beadle 1940;Busse et al 2005;Monsanto and Agee 2008;Varner et al 2009). …”
Section: Discussionmentioning
confidence: 99%